Beginning PL/SQL : from novice to professional - Bales, Donald; SpringerLink (Online service) (Berkeley, CA : Springer, 2007)
A guide to the PL/SQL programming language cover such topics as writing stored functions, using singletons and cursers, debugging, and testing.
Includes index.
Keywords: Oracle (computer file); PL/SQL (Computer program language); Relational databases